2018
DOI: 10.1111/ggi.13258
|View full text |Cite
|
Sign up to set email alerts
|

High plasma adiponectin levels are associated with frailty in a general old‐old population: The Septuagenarians, Octogenarians, Nonagenarians Investigation with Centenarians study

Abstract: The present study showed that higher plasma adiponectin levels were associated with frailty status in older Japanese adults in the general population. Further longitudinal study is essential to clarify the role of plasma adiponectin in the progression of frailty. Geriatr Gerontol Int 2018; 18: 839-846.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 31 publications
(54 reference statements)
1
20
0
1
Order By: Relevance
“…It was reported that elevated circulating APN levels were an independent markers of both myocardial infarction (MI) and all-cause mortality in male patients undergoing coronary angiography 37 . Such inverse correlation with circulating APN levels has been also reported on muscle weakness in elderly people 31,32 , muscle mass and strength in elderly heart failure patients 33 . Here we have revealed that high circulating APN levels in mice were not inhibitory but promotive for muscle regeneration at least under high angiotensin II levels, suggesting that above mentioned higher circulating APN in elderly patients especially with heart failure may not be causative for their associated muscle weakness and loss of muscle mass.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It was reported that elevated circulating APN levels were an independent markers of both myocardial infarction (MI) and all-cause mortality in male patients undergoing coronary angiography 37 . Such inverse correlation with circulating APN levels has been also reported on muscle weakness in elderly people 31,32 , muscle mass and strength in elderly heart failure patients 33 . Here we have revealed that high circulating APN levels in mice were not inhibitory but promotive for muscle regeneration at least under high angiotensin II levels, suggesting that above mentioned higher circulating APN in elderly patients especially with heart failure may not be causative for their associated muscle weakness and loss of muscle mass.…”
Section: Discussionsupporting
confidence: 62%
“…Recent clinical studies have shown that plasma APN levels inversely correlated with muscle weakness in elderly people 31,32 , muscle mass and strength especially in heart failure patients 33 . T-cad is expressed abundantly in skeletal muscle in addition to above mentioned vascular endothelium and heart 21 .…”
Section: Introductionmentioning
confidence: 99%
“…This topic has been vigorously addressed in our longitudinal cohort study for old people, known as the SONIC (i.e., septuagenarians, octogenarians, and non-agenarians investigation with centenarians) study, which investigated the age differences and similarities in factors influencing healthy aging and psychological well-being, including psychological (i.e., cognition, change in emotion and compensation, personality, and psychological development); social (i.e., socio-economic status and social relationship); and medical, dental, and nutritional aspects (61). In 353 community-dwelling older adults of approximately 83 years, Nagasawa et al deduced an association between circulating adiponectin and frailty status according to the cardiovascular health study criteria (62). The investigators found significantly higher adiponectin levels in frail subjects than in their non-frail counterparts.…”
Section: Adiponectin and Frailty In The Very Old: Another Paradoxmentioning
confidence: 99%
“…Adipokines secreted by adipose tissues such as adiponectin were found to be associated with frailty. 5 Other adipokines such as vaspin and leptin were found to be associated with chronic diseases, but their association with frailty was not yet studied. Finding the biological correlates would allow physicians to identify frailty, monitor the progression and efficacy of interventions, and delay the onset of frailty and occurrence of disability.…”
Section: Introductionmentioning
confidence: 99%